Analisis Mekanisme Purchasing Terhadap Proses Pengadaanbarang Housekeeping Department Pada Hotel Four Point Bysheraton Medan - Siregar, Muhammad Ichiro Al Kindy; Rosari, Dina; Taviani, Tina (Tourism, Hospitality And Culture Insights Journal, 2023)
The purpose of this study is to describe and explain the role of Purchasing in procuring goods at Four Point by Sheraton Medan Hotel. The results of the research are expected to be a reference and consideration for the Finance Department and more precisely for the Purchasing Department regarding the role of Purchasing in the procurement of Housekeeping Department goods. Purchasing is an important part of an organization where Purchasing's job is to provide all thegoods needed by the company starting from physical goods, services and services This type of research uses case studies of data collected by observation, interviews, documentation,and literature study techniques. The variables are the Purchasing Mechanism and Procurement of Goods (Y). this research itself uses a qualitative approach with descriptive analysis. The results of the analysis of observations and interviews conducted with Mr. Agus as Purchasing Officer stated that the role of Purchasing in the process of ordering goods, procuring goods, and distributing Housekeeping Department goods must be in accordance with the Standard Operational Procedure (SOP). In the Supplier selection process must be carried out in a transparent manner and must have at least 3 suppliers in order to avoid the unavailability of goods requested by the user. Behind that in order to minimize sudden requests made by users, of course this will help the work / activities of a Purchasing without having to make direct purchases.